Cell shape and interaction defects in -spectrin mutants of Drosophila melanogaster. - Lee, J.K.; Coyne, R.S.; Dubreuil, R.R.; Goldstein, L.S.B.; Branton, D. (Journal of Cell Biology, 1993)
We show that the alpha-spectrin gene is essential for larval survival and development by characterizing several alpha-spectrin mutations in Drosophila. P-element minigene rescue and sequence analysis were used to identify the alpha-spectrin gene as the l(3)dre3 complementation group of the Dras-Roughened-ecdysoneless region of chromosome 3 (Sliter et al., 1988). Germ line transformants carrying an alpha-spectrin cDNA, whose expression is driven by the ubiquitin promoter, fully rescued the first to second instar lethality characteristic of the l(3)dre3 alleles. The molecular defects in two gamma-ray-induced alleles were identified. One of these mutations, which resulted in second instar lethality, contained a 73-bp deletion in alpha-spectrin segment 22 (starting at amino acid residue 2312), producing a premature stop codon between the two EF hands found in this segment. The second mutation, which resulted in first instar lethality, contained a 20 base pair deletion in the middle of segment 1 (at amino acid residue 92), resulting in a premature stop codon. Examination of the spectrin-deficient larvae revealed a loss of contact between epithelial cells of the gut and disruption of cell-substratum interactions. The most pronounced morphological change was seen in tissues of complex cellular architecture such as the middle midgut where a loss of cell contact between cup-shaped cuprophilic cells and neighboring interstitial cells was accompanied by disorganization of the cuprophilic cell brush borders. Our examination of spectrin deficient larvae suggests that an important role of non-erythroid spectrin is to stabilize cell to cell interactions that are critical for the maintenance of cell shape and subcellular organization within tissues.